GROUP B STREPTOCOCCUS CIRCUMVENTS NEUTROPHILS AND NEUTROPHIL EXTRACELLULAR TRAPS DURING AMNIOTIC CAVITY INVASION AND PRETERM LABOR - Boldenow, Erica (Sci Immunol, 2016)
Preterm birth is a leading cause of neonatal morbidity and mortality. Although microbial invasion of the amniotic cavity (MIAC) is associated with the majority of early preterm births, the temporal events that occur during MIAC and preterm labor are not known. Group B Streptococci (GBS) are β-hemolytic, gram-positive bacteria, which commonly colonize the vagina but have been recovered from the amniotic fluid in preterm birth cases. To understand temporal events that occur during MIAC, we utilized a unique chronically catheterized nonhuman primate model that closely emulates human pregnancy. This model allows monitoring of uterine contractions, timing of MIAC and immune responses during pregnancy-associated infections. Here, we show that adverse outcomes such as preterm labor, MIAC, and fetal sepsis were observed more frequently during infection with hemolytic GBS when compared to nonhemolytic GBS. Although MIAC was associated with systematic progression in chorioamnionitis beginning with chorionic vasculitis and progressing to neutrophilic infiltration, the ability of the GBS hemolytic pigment toxin to induce neutrophil cell death and subvert killing by neutrophil extracellular traps (NETs) in placental membranes in vivo facilitated MIAC and fetal injury. Furthermore, compared to maternal neutrophils, fetal neutrophils exhibit decreased neutrophil elastase activity and impaired phagocytic functions to GBS. Collectively, our studies demonstrate how a unique bacterial hemolytic lipid toxin enables GBS to circumvent neutrophils and NETs in placental membranes to induce fetal injury and preterm labor.